Identification of Immune Subtypes of Lung Squamous Cell Carcinoma by Integrative Genome-Scale Analysis - Yin, Liyuan; Zhang, Wen; Pu, Dan; Zhai, Xiaoqian; Lin, Yiyun; Wu, Qiang; Chang, Tangel; Hu, Jia; Li, Yan; Zhou, Qinghua (Frontiers in Oncology, 2022)
Background: Characterization of the tumor microenvironment is helpful to understand the tumor immune environment of lung cancer and help predict the prognosis. Methods: First, immune subtypes were identified by Consensus subtype among lung squamous carcinoma (LUSC) patients. Immune cell infiltration was evaluated by CIBERSORT and ESTIMATE analysis. Then, based on differentially expressed genes (DEGs) identified, a risk score model was constructed. Finally, gene FPR1 was validated by using YTMLC-90. Findings: LUSC samples were divided into four heterogeneous immune subtypes, with significantly different prognosis with subtype 4 having poorest overall survival (OS). Immune infiltration score showed that subtype 4 was characterized as immune enriched and fibrotic, while subtype 3 was tumor enriched. DEGs analysis showed that up-regulated genes in subtype 4 were enriched of neutrophil and exhausted T cell related biological processes. Based on a univariate Cox regression model, prognostic 7 immune-related genes were combined to construct a risk score model and able to predict OS rates in the validation datasets. Wound healing and transwell assay were conducted to evaluate the invasion property after activating the gene FPR1. Interpretation: The analysis of tumor immune microenvironments among LUSC subtypes may provide new insights into the strategy of immunotherapy.